Changing paradigm of scrub typhus infection in children: A study from a tertiary care center of Eastern India - Bhattacharya, Urmimala; Pal, Sumita; Paria, Soumyadip; Basu, Kaushambi (Asian Journal of Medical Sciences, 2024)
Background: Scrub typhus, a zoonotic disease, is transmitted to humans by the bite of larval trombiculid mite. Keeping in view the morbidity and mortality associated with undiagnosed cases (due to both lack of specific diagnostic tests and ignorance about the disease), the disease deserves a special mention. Aims and Objectives: The aims and objectives of the study were to assess complications and atypical manifestations of scrub typhus fever in this subpopulation and to assess the prognosis of patients presenting with atypical manifestations/complications. Materials and Methods: This is a longitudinal observational study on the basis of clinical and laboratory evidence at Department of Pediatrics, Calcutta-National-Medical College and Hospital, Kolkata, West Bengal, from March 2021 to February 2022. Children between >28 days and <12 years with atypical manifestations of scrub typhus who were scrub immunoglobulin (Ig)M positive (Serum and/or cerebrospinal fluid) were included in the study. Results: Of the 120 scrub typhus IgM-positive patients admitted in 1 year, complications present in 35%. These patients developed encephalitis, encephalomyelitis, neurological deficits, myocarditis, disseminated intravascular coagulation, acute kidney injury, atypical pneumonia, acute respiratory distress syndrome, acute encephalitis syndrome (23.8%), myocarditis with/without heart failure (14.3%), and multi-inflammatory syndrome in children with/without severe acute respiratory syndrome coronavirus 2 IgG (14.2%). There is a statistically significant association between the duration of fever at admission and pediatric intensive care unit (PICU) admission, the longer the fever duration at admission, the higher the rate of complications and thus PICU admission. Conclusion: Scrub typhus infection has expanded its various forms, presenting in various atypical manifestations alongside the common clinical features. Multiple cases of multiorgan involvement in the form of multi-inflammatory syndrome and hemophagocytic lymphohistiocytosis have been reported in the background of COVID-19 infection, alongside a significant percentage of scrub typhus infection reported in infancy. Thus, early detection is important to start intervention.